Policy Implementation Green Public Procuremen in Sustainable Development in South Kalimantan Province - Husin Ansari; Nurliah Nurdin; Irwan Tahir; Dedeh Maryani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The increasingly massive consumption of illegal paper, plastic and wood products contributes to increasing the potential for environmental damage. However, awareness of using environmentally friendly products is still low, including in government circles. In order to overcome these problems, the Provincial Government of South Kalimantan is the leading regional government that implements the Green Public Procurement (GPP) to align with sustainable development goals. However, the implementation of the policy is seen as still not optimal. This study intends to analyze the causes of the non-optimal implementation of GPP policies in South Kalimantan, which then formulates a model for implementing GPP policies. The qualitative research method was used by researchers with research data collected through interviews, observation and documentation studies techniques coding assisted by the Nvivo 12 program and combined descriptive analysis referring to the GPP framework theory from Akenroye, et.al. (2013) and Meter and Horn's (1975) policy implementation model theory. The study found that: 1) Policy implementation was not optimal due to the absence a road map in the policy action plan, lack of understanding and implementation of the GPP legal framework, low capacity of GPP regulatory and implementing authorities, lack of ecolabel environmentally friendly products, and lack of massive and intense socialization. IT DOESN'T MATTER; 2) The Sustainable GPP Policy Implementation Model is formulated by researchers as a model that emphasizes the alignment of policy implementation with environmental, social, and economic oriented sustainable development goals. The model consists of aspects. Researchers put forward suggestions: 1) academic suggestions, further research needs to develop the object of study and the theme of Green Public Procurement in the procurement sector of other environmentally friendly goods and services such as green building and green road construction; 2) practical advice, the Provincial Government of South Kalimantan needs to develop a comprehensive Standard Operating Procedure as a technical guide for parties related to the procurement of government goods and services in implementing sustainable GPP.